2007
DOI: 10.1095/biolreprod.107.060681
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Arterial Tone During Pregnancy: The Effect of the Bioactive Metabolite Sphingosine-1-Phosphate1

Abstract: Sphingosine-1-phosphate (S1P) is a potent bioactive lipid that has been implicated in cardiovascular disease. The objective of the present study was to determine the vasoactive effects and underlying mechanisms of S1P on adult human maternal arteries. The isometric tensions of the omental and myometrial arteries isolated from normal pregnant women at term were assessed in response to incremental doses of S1P in the presence or absence of the nitric oxide (NO) synthase inhibitor N(G)-nitro-L-arginine methyl est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(60 reference statements)
1
9
0
1
Order By: Relevance
“…Recently, it has been reported that S1P inhibits cytotrophoblast differentiation and could be involved in the pathogenesis of preeclampsia in humans (47). Furthermore, S1P has been shown to induce a dose-dependent vasoconstriction in human uterine arteries during pregnancy (48). Given these results and the results in our study, disturbance in sphingolipid metabolism may be relevant to human reproductive failure.…”
Section: Figure 10supporting
confidence: 78%
“…Recently, it has been reported that S1P inhibits cytotrophoblast differentiation and could be involved in the pathogenesis of preeclampsia in humans (47). Furthermore, S1P has been shown to induce a dose-dependent vasoconstriction in human uterine arteries during pregnancy (48). Given these results and the results in our study, disturbance in sphingolipid metabolism may be relevant to human reproductive failure.…”
Section: Figure 10supporting
confidence: 78%
“…The present study is important for identifying (i) that estrogen differentially regulates human uterine and placental vascular tone; (ii) the potential of ER-specific agonists to act as tissue-specific modulators of human uteroplacental vascular tone; (iii) adding to an evolving narrative in the literature whereby circulatory, or locally produced, factors may differentially alter the tone of human myometrial or placental arteries (Hemmings et al , 2006; Hudson et al , 2007; Corcoran et al , 2012). It is of interest that subcutaneous arteries isolated from post-menopausal healthy women relaxed more to PPT than 17β-estradiol and the effects of either agent were unaltered by NOS inhibition (Cruz et al , 2008)—results that were different to that which we observed in maternal myometrial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S1P signaling regulates the myogenic response to pressure. (Coussin et al, 2002;Salomone et al, 2003;Scherer et al, 2006), as well as in human resistance arteries, including omental and myometrial arteries from pregnant women (Hudson et al, 2007), placenta and stem villous arteries (Hemmings et al, 2006), and porcine retinal arterioles (Kamiya et al, 2014). Mouse S1P 10 nM-30 mM + eNOS (L-NAME) Roviezzo et al (2006) Akt, protein kinase B; BAPTA, 1,2-bis(o-aminophenoxy)ethane-N,N,N9N9-tetraacetic acid; FTY720-P, FTY20 phosphate; L-NAME, L-N G -nitroarginine methyl ester; N.R., not reported; PTX, pertussis toxin; SD, Sprague Dawley; 2, absence of endothelium; +, presence of endothelium.…”
Section: S1p In Vascular and Myogenic Tone Regulationmentioning
confidence: 99%